Comparación de la educación a distancia con la educación presencial: modelos de educación, diseños instruccionales y rendimiento académico de los alumnos (A comparative analysis between distance vs. traditional education: teaching models, instructional learning designs, and academic performance) - Jardines Garza, Francisco Javier (Facultad de Contaduría Pública y Administración U.A.N.L., 2010)
Abstract. In this paper we present a comparative analysis between distance education vs. traditional education trough three issues: teaching models, instructional design, and academic performance. In each issue we highlight the follow topics: a) teaching models: distance education is growing, however we do not expect the elimination of the traditional education, b) Instructional design: this issue is different between distance education vs. traditional education, and c) academic performance: there is no significant difference in academic results for students who develop a distance learning courses and students taking the same courses in a classroom.